Contribution of Educational Institutions in the Preservation of Traditional Culture Karawitan Java - Dzakia, Shinta Nur; Saputri, Indri Dewi; Sari, Rani Puspita; Hayati, Kulsum Nur (Jurnal Smart Paud, 2024)
Culture as a state identity must always be preserved so that it remains alive and relevant for every generation of society. Indonesia has a variety of cultures, including traditional music on the island of Java, namely Karawitan Art. The process of cultural inheritance can be through educational institutions which are leading institutions that are in direct contact with the nation's generation. So this research was taken to describe the efforts made by educational institutions in contributing to preserving the traditional culture of karawitan art concretely.  A study designed using a qualitative approach with a case study type . Data was obtained through observation, interviews and documentation. The informants are educators and trainers. The number of students is 26 children, all of whom participated in karawitan activities. This karawitan group is named "Karawitan Cilik". The learning method of karawitan art uses the habituation method. Learning the art of karawitan is proven to support children's development, including in physical, motor, cognitive, social-emotional, moral, language and art aspects. The learning of karawitan art carried out by educational institutions is a form of contribution to preserving traditional culture in the surrounding environment. In addition, this activity can also be a meaningful learning for students.